Control or non-control state: that is the question! An asynchronous visual P300-based BCI approach. (14th January 2015) - Pinegger, Andreas; Faller, Josef; Halder, Sebastian; Wriessnegger, Selina C; Müller-Putz, Gernot R
Abstract: Objective. Brain–computer interfaces (BCI) based on event-related potentials (ERP) were proven to be a reliable synchronous communication method. For everyday life situations, however, this synchronous mode is impractical because the system will deliver a selection even if the user is not paying attention to the stimulation. So far, research into attention-aware visual ERP–BCIs (i.e., asynchronous ERP–BCIs) has led to variable success. In this study, we investigate new approaches for detection of user engagement. Approach. Classifier output and frequency-domain features of electroencephalogram signals as well as the hybridization of them were used to detect the userʼs state. We tested their capabilities for state detection in different control scenarios on offline data from 21 healthy volunteers. Main results. The hybridization of classifier output and frequency-domain features outperformed the results of the single methods, and allowed building an asynchronous P300-based BCI with an average correct state detection accuracy of more than 95%. Significance. Our results show that all introduced approaches for state detection in an asynchronous P300-based BCI can effectively avoid involuntary selections, and that the hybrid method is the most effective approach.